2007
DOI: 10.1037/0894-4105.21.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electroencephalographic profiles for children with autistic spectrum disorder.

Abstract: The present study examined quantitative electroencephalographic (QEEG) profile for children with autistic spectrum disorder (ASD). Five-minute QEEG data were obtained from 90 normal controls (NCs) and 66 children with ASD. Spectrum analyses revealed that ASD children showed significantly less relative alpha and more relative delta than NC. Specifically, 26% of ASD children and 2% of NCs showed 1.5 SDs of relative alpha below the normative mean. Children with this QEEG profile had 17 times the risk of having AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 45 publications
4
59
1
5
Order By: Relevance
“…First, significant differences in the alpha band were shown by five studies with relaxed eyes open condition (41, 42, 50, 54, 55). While four studies show a decrease in absolute spectral power in ASD in children of similar ages (41, 42, 50, 55), another showed elevated absolute alpha power in adults (54). The inconsistencies might be attributed to the age differences between participants and differing developmental trajectories in children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…First, significant differences in the alpha band were shown by five studies with relaxed eyes open condition (41, 42, 50, 54, 55). While four studies show a decrease in absolute spectral power in ASD in children of similar ages (41, 42, 50, 55), another showed elevated absolute alpha power in adults (54). The inconsistencies might be attributed to the age differences between participants and differing developmental trajectories in children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…They found that children with ASD showed significantly less relative alpha power. This was not specific to restricted location(s) but was a widespread pattern (Chan et al 2007). Less alpha may indicate a brain that does not rest appropriately, which is perhaps the flip side of the picture of spindling beta and low SMR frequently found in clients with AS.…”
Section: Nfb Trainingmentioning
confidence: 95%
“…Relative power was used for analyses on the theta band based on previous findings linking relative power measures to better estimates for the theta band because (1) relative power measurements tend to give larger estimates for the dominant frequency range (Klimesch 1999), and (2) individual variations are eliminated by computing the proportion of an individual frequency band relative to the others (Chan et al 2007). To examine the changes in relative theta power in response to the two treatment conditions, a 2 9 29 4 (Condition9 Time9 Area) threeway analyses of variance (ANOVA) with repeated measures was performed, with Condition (two levels: music, TBRT), Time (two levels: baseline, during treatment condition), and Area (four levels: anterior, posterior, left, right) as within-subject factors.…”
Section: Relative Thetamentioning
confidence: 99%